Photon irradiation response of photonic crystal fibres and flat fibres at radiation therapy doses - Hashim, Suhairul (Elsevier, 2014)
Radiation effects of photon irradiation in pure Photonic Crystal Fibres (PCF) and Flat fibres (FF) are still much less investigated in thermoluminescense dosimetry (TLD). We have reported the TL response of PCF and FF subjected to 6 MV photon irradiation. The proposed dosimeter shows good linearity at doses ranging from 1 to 4 Gy. The small size of these detectors points to its use as a dosimeter at megavoltage energies, where better tissue-equivalence and the Bragg–Gray cavity theory prevails.